Suppose X has the poisson pmf pX(n) = λnexp(-λ)/n!, n>=0 and λ=5

and Y has the poisson pmf

pY(n)=μnexp(-μ)/n! n>=0 and μ=7

Let Z=X+Y, find

- pz(7)
- Let A be the event that z=6. Find pY|A(4)

Printable View

- Mar 28th 2009, 05:41 AMessedra[SOLVED] Sum of two Poissons
Suppose X has the poisson pmf pX(n) = λnexp(-λ)/n!, n>=0 and λ=5

and Y has the poisson pmf

pY(n)=μnexp(-μ)/n! n>=0 and μ=7

Let Z=X+Y, find

- pz(7)
- Let A be the event that z=6. Find pY|A(4)

- Mar 28th 2009, 01:23 PMmr fantastic
Are X and Y independent? If so, here's your starting point: Sum of two independent Poisson random variables

- Mar 28th 2009, 05:21 PMessedra
I think they are independent but the point is, I don't know how to apply the formula.(Sadsmile)

- Mar 28th 2009, 06:14 PMmr fantastic
- Mar 29th 2009, 02:59 AMessedra